Penguatan Kepercayaan Diri dan Motivasi Belajar Siswa Sekolah Menegah Pertama Melalui Kegiatan Outbound Berbasis Experiential Learning di Tanwirul Qulub, Lombok Tengah - Dinis Cahyaningrum; Ni Wayan Adelia Mutiara Asri; Isra Dewi Kuntary Ibrahim; Baiq Krisnina Maharani Putri; Khairul Mujahidi (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The issues of low self-confidence and insufficient learning motivation among junior high school students in rural contexts represent significant challenges for character development and educational achievement. This condition is particularly evident at SMP Tanwirul Qulub, Central Lombok, where the majority of students come from farming families with limited socio-economic backgrounds. In response, this community engagement program was designed to enhance students’ self-confidence, foster learning motivation, and improve social competencies through outbound activities grounded in experiential learning. The intervention was structured using Kolb’s Experiential Learning Model, which consists of four sequential stages: Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation. The program was implemented in three sessions, including ice breaking, core games (Seven Boom and Group Vampire), and reflective discussions. The participants comprised 18 students aged 12–15 years. The findings revealed noticeable improvements, as demonstrated by students’ greater involvement in discussions, increased willingness to express opinions, and enhanced awareness of the value of education. These outcomes suggest that outbound-based experiential learning can serve as a strategic and transformative approach for character formation and motivation enhancement in educational settings with limited resources.